2022
DOI: 10.1186/s12879-022-07163-2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C seroprevalence among people living with HIV/AIDS and pregnant women in four provinces in Cambodia: an integrated bio-behavioral survey

Abstract: Background Understanding the extent of viral hepatitis burden in specific subgroups, such as pregnant women and people living with HIV/AIDS (PLWHA), and their geographic distribution is essential for evidence-informed policy and mobilizing resources for targeted treatment and prevention efforts. However, in Cambodia, the epidemiology of hepatitis C remains uncertain. We estimated the hepatitis C virus (HCV) burden and transmission risk factors among PLWHA and pregnant women attending antenatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Several other factors such as limited education, tendency of prescribers to recommend and participant’s personal preference of injection and the study population could be responsible for higher rates being reported in our study compared with others. However, these seemed consistent with a recently published paper which found high hepatitis C prevalence among Cambodian population that is likely due to medical injections 16. High prevalence of medical injection (ranging from 30% to 68%) had also been reported across studies conducted in South Asia 17.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Several other factors such as limited education, tendency of prescribers to recommend and participant’s personal preference of injection and the study population could be responsible for higher rates being reported in our study compared with others. However, these seemed consistent with a recently published paper which found high hepatitis C prevalence among Cambodian population that is likely due to medical injections 16. High prevalence of medical injection (ranging from 30% to 68%) had also been reported across studies conducted in South Asia 17.…”
Section: Discussionsupporting
confidence: 90%
“…Our work is one of the few studies which examined injection practices among PLWH over the past decade. Another study was conducted in 2016 (a year prior to when our study had started) 16. Regardless, additional studies are necessary in order to confirm the findings from our work and understand the true underlying injection practices among PLWH.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In the Asia-Pacific region, the prevalence of HCV co-infection among adult PLHIV ranges from 2.9% to 80% depending on the characteristics of the study population [4][5][6][7][8][9][10][11][12]. Injecting drug use is consistently associated with an increased risk of HCV coinfection, [10,[13][14][15][16] and men who have sex with men (MSM) and sex workers living with HIV are also at increased risk [17,18].…”
Section: Introductionmentioning
confidence: 99%